(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Information received from a person accused of an offence is always of immense importance, it may be in the form of confession or statement. The rule which exclude confession made to police is a rule based on public policy. Section 27 of Indian evidence Act, 1872 is exception to this rule. An information given by accused person in police custody leading to discovery of a fact is admissible and relevant. It is based on doctrine of confirmation by subsequent finding. Any statement admissible under this section is admissible against the person accused giving information and not against any other person. The provisions of section 27 are constitutionally valid and valuable for criminal justice system.